A study on customer's perception of online banking and e-service quality among Chennai customers. (2017) - Kumar, G.; Shenbagaraman, V.M.
The information technology advancements in India have more impact on Indian banking industry. Now, the internet is the most preferred medium which is used between customer and the bank. Due to technological advancements in India, the internet availability and the internet usage is increased largely. The internet medium is rapidly changing the traditional face to face banking to online banking. To study the quality of the bank, it is necessary to study the e-service quality of banks. This paper deals with customer's perception of online banking and e-service quality and its influence on customer satisfaction. The quantitative research design is used for this study. The study was conducted using self administered questionnaire. The sampling method used for the study is random sample method .The sample size of 98 is taken for the study. The study was conducted in Chennai City of India. The factor analysis and multiple regressions were used to analyse the data. The findings from this study reveal that the variables compensation and recovery, access, personalisation and assurance play a major role in online banking service quality. Also, the study reveals that the customer satisfaction leads to customer loyalty.